Resources supporting entrepreneurial orientation in multigenerational family firms. (29th November 2010) - Irava, Wayne; Moores, Ken
We examine entrepreneurship in multigenerational family firms. Specifically, we employ theoretical lenses drawn from both entrepreneurship (entrepreneurial orientation) and strategy (resource-based view) to develop an integrated model of transgenerational entrepreneurship. Following a review of the literature in these fields we develop propositions that articulate connections between a family firm's unique bundle of resources (familiness), its entrepreneurial orientation (EO), and the achievement of its non-financial performance objectives (NFPO). In this way the paper not only contributes to the debate concerning the link between family background and entrepreneurial behaviour but also helps clarify the broad construct familiness in terms of the nature of resources within the unique bundle.